Workplace thriving in China. Issue 5 (5th August 2019) - Jiang, Zhou; Jiang, Yiqi; Nielsen, Ingrid
Abstract : Purpose: Workplace thriving is a psychological state that promotes employee health and development. In addition to presenting a useful instrument that captures the nature of a thriving work life in China, the purpose of this paper is to investigate important factors that influence one's thriving status within this national context. Design/methodology/approach: Using diverse approaches across different samples, Study 1 contextualized the content of a workplace thriving scale (WTS) to fit the Chinese context. Study 2 tested the effects of learning goal orientation, exploration at work and role ambiguity on workplace thriving, employing a mediation model. As a supplement, Study 3 examined the test–retest reliability of workplace thriving. Findings: Study 1 confirmed that in the Chinese setting, workplace thriving is a higher order construct represented by both a sense of learning and a sense of vitality. Study 2 found that learning goal orientation and exploration at work fostered thriving, while role ambiguity reduced thriving. Also, exploration mediated the relationship between learning goal orientation and thriving. Study 3 verified that the WTS was reliable over time in the Chinese setting, further increasing the reliability of results from Studies 1 and 2. Originality/value: By rigorously and formally contextualizing the concept/construct of workplace thriving in China, this paper is informative for future research on thriving at work in Eastern cultures.